Ford Model ""T"" car no. 2, winner of the trans-continental race from New York to Seattle arrival, Alaska Yukon Pacific Exposition, Seattle, June 1909. - Nowell, Frank H., 1864-1950 (1909)
One of two cars entered by the Ford Motor Company in the contest for M. Robert Guggenheim trophy. Driven by Bert Scott and mechanic Frank Smith. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number